2016
DOI: 10.1111/geoa.12135
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of karst depressions on a mediterranean karst massif

Abstract: Dolines are the most typical landform in karst landscapes. They play an important role in karst hydrogeology; they are effective sediment traps that provide information about past climates and karst evolution, and can also be indicators of tectonic activity. The morphometic analysis of those depressions can help in their study and interpretation. However, detailed identification and delineation of dolines becomes increasingly difficult when the study area is very large, of limited access or covered by vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…These figures confirm the intuitive similarity of the spatial patterns in Figure 4 and they reflect the universality of the fractal law: very different physical processes give rise to similar spatial patterns. Pardo-Igúzquiza et al (2016c) and Yizhaq et al (2017) have recently demonstrated the fractal character of sinkholes.…”
Section: Fractals In the Exokarstmentioning
confidence: 98%
“…These figures confirm the intuitive similarity of the spatial patterns in Figure 4 and they reflect the universality of the fractal law: very different physical processes give rise to similar spatial patterns. Pardo-Igúzquiza et al (2016c) and Yizhaq et al (2017) have recently demonstrated the fractal character of sinkholes.…”
Section: Fractals In the Exokarstmentioning
confidence: 98%
“…Esse tipo de análise quantitativa retira o fator subjetividade nas análises comparativas entre regiões cársticas (Ferrari et al, 1998) e permite revelar dados e informações anteriormente não observadas, possibilitando novas hipóteses (Ford e Williams, 2007). Nesse sentido diversos trabalhos internacionais tratam sobre as formas clássicas ou uso de novas tecnologias de mapeamento de dolinas, análises morfométricas e interpretações ambientais correlatas (Denizman, 2003;Seale et al, 2008;Siart et al, 2009;Faulkner et al, 2013;Kovačič e Ravbar, 2013;Pardo-Igúzquiza et al, 2013;Zhu et al, 2014;Kobal et al, 2015;Aguilar et al, 2016;Gessert, 2016;Keskin e Yılmaz, 2016;Lee et al, 2016;Pardo-Igúzquiza et al, 2016;Telbisz et al, 2016;Wu et al, 2016;Zhu e Pierskalla, 2016;Čeru et al, 2017;Wall et al, 2017;Cahalan e Milewski, 2018;Chen et al, 2018;Harris et al, 2018;Hofierka et al, 2018;Öztürk et al, 2018).…”
Section: Análises Morfométricas De Depressões Cársticasunclassified
“…In many cases, previous studies have shown that the doline areas within a study terrain are best characterized by a lognormal distribution [31,[34][35][36]. However, it has also been suggested that the cumulative distribution of doline areas can be well described by a power function, which may be based on fractal properties [37][38][39]. For a more detailed interpretation of this approach, see [39].…”
Section: Introductionmentioning
confidence: 99%